2022
DOI: 10.1021/acs.langmuir.2c01593
|View full text |Cite
|
Sign up to set email alerts
|

Orientational Dynamics of Magnetic Iron Oxide Nanoparticles in a Hydrogel: Observation by Magnetic Linear Dichroism under Oscillating Field

Abstract: For the success of biomedical applications of magnetic iron oxide nanoparticles (MION), such as magnetic hyperthermia and magnetic particle imaging, it is essential to understand the orientational dynamics of MION in a complex fluid under an alternating field. Here, using the magnetic linear dichroism (MLD) measurement, we directly observed the orientational behavior of MION in a hydrogel under a damped oscillating magnetic field (DOMF) of 33 kHz in frequency. Hydrophobically modified ethoxylated urethane (HEU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…294 Here, again, the aggregation state of MNPs will severely affect the interpretation of the observation. Optical polarization measurements of the magnetic orientation of MNPs will become a promising method to measure the viscosity of the nano-environment, 232 the stability of MNPs in solution, and the aggregation dynamics of nanoparticles given that the optical transition moment of MNPs is parallel to the easy axis of the magnetic moment of MNP 295 and highly sensitive to the rotational relaxation dynamics. 228 Electromagnetophoretic force was applied for the size separation and adsorption-desorption chromatography of microparticles, 238 but more applications should be investigated.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…294 Here, again, the aggregation state of MNPs will severely affect the interpretation of the observation. Optical polarization measurements of the magnetic orientation of MNPs will become a promising method to measure the viscosity of the nano-environment, 232 the stability of MNPs in solution, and the aggregation dynamics of nanoparticles given that the optical transition moment of MNPs is parallel to the easy axis of the magnetic moment of MNP 295 and highly sensitive to the rotational relaxation dynamics. 228 Electromagnetophoretic force was applied for the size separation and adsorption-desorption chromatography of microparticles, 238 but more applications should be investigated.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…In addition, a recent study showed that this method will be useful for measuring the local viscous environment around the MNPs. 232…”
Section: Application Of Magnetic Torquementioning
confidence: 99%
“…(1) polyhedral oligomeric silsesquioxanes (POSS) nanoparticles with the diameter d on the order of 1 to 3 nm, 27,40,46 (2) quantum dots (QDs) with 2 nm < d < 10 nm, 36,67 (3) gold nanoparticles with 5 nm < d < 400 nm, 11,12,14,19,34,39,43,49,50,55,56,63,78 (4) magnetic nanoparticles with 5 nm < d < 20 nm, 18,31,37,38,51,52,62,64,70,71,76,80 (5) silica (SiO 2 ) nanoparticles with 5 nm < d < 50 nm, 26,29,30,44,48,57,60,61,74,81 (6) polystyrene nanoparticles with 20 nm < d < 2000 nm, 13,16,17,22,33,35,53,65,66,68,69,72 (7) nanorods with dimensions from (1) nm to (100) nm made of Au, magnetic elements and their dioxides, or titanium dioxide (TiO 2 ). 15,…”
Section: Introductionmentioning
confidence: 99%
“…The development of nanoparticle chemistry in recent years has enabled the synthesis of nanoparticles with well-controlled size, shape, and surface chemistry, yielding a library of nanoparticles available for investigating fundamental scientific problems and exploring nanoparticle-based applications. Nanoparticles commonly used in the studies of nanoparticle dynamics in a polymer matrix include polyhedral oligomeric silsesquioxanes (POSS) nanoparticles with the diameter d on the order of 1 to 3 nm, ,, quantum dots (QDs) with 2 nm < d < 10 nm, , gold nanoparticles with 5 nm < d < 400 nm, ,,,,,,,,,,,, magnetic nanoparticles with 5 nm < d < 20 nm, ,…”
Section: Introductionmentioning
confidence: 99%